TMEM65 is a mitochondrial inner-membrane protein - Nishimura,Naotaka; Gotoh,Tomomi; Oike,Yuichi; Yano,Masato (PeerJ, 2014)
It has been reported that the expression of TMEM65 is regulated by steroid receptor RNA activator (SRA). To date, however, the localization and function of TMEM65 remained unknown. We analyzed the intracellular localization of TMEM65. Immunoblot and immunostaining analysis revealed mitochondrial localization of TMEM65. Alkali extraction analysis and digitonin extraction test using isolated mitochondria revealed that TMEM65 is an integral membrane protein that localizes to the inner-membrane of mitochondria. Analysis using deletion mutants of TMEM65 suggested that the N-terminal region (1–20) of this protein is sufficient for mitochondrial targeting and that this mitochondrial targeting signal (MTS) is cleaved between the amino acid positions 35 and 64, which contain a putative recognition site of matrix processing protease (MPP). Together, these results suggest that TMEM65 is imported into the mitochondria, integrated into mitochondrial inner-membrane, and processed into its mature form by an MPP.
Keywords: Inner-membrane; TMEM65; Mitochondria; Processing; Mitochondrial targeting signal (MTS)